Paradigma Saintifik dalam Penafsiran Ayat-Ayat Kauniyah: Telaah atas Interpretasi Agus Purwanto terhadap QS. Al Anbiyā’: 30 - Rasyid Hidayatullah; Teddy Noor Hidayat (AT-TAKLIM: Jurnal Pendidikan Multidisiplin, 2025)
The relationship between divine revelation and science in understanding ayat kauniyah (verses about the natural world) represents a unique area of study amid the dominance of textual and theological interpretations in Islamic tradition. This topic was chosen because it reflects an effort to reconstruct the paradigm of Islamic scholarship through the thought of Agus Purwanto, who views the Qur’an not merely as a spiritual text but as an epistemological source for the development of modern scientific knowledge. This research draws on various primary and secondary sources, including the Qur’an, Tafsir al-Mishbah by M. Quraish Shihab as the main reference for interpreting QS. Al-Anbiyā’ [21]:30, as well as Agus Purwanto’s works such as Nalar Ayat-Ayat Semesta, which form the analytical foundation for integrating revelation and science. Contemporary references on scientific exegesis and the concept of theo-science are also employed. The study aims to explain how Agus Purwanto’s concept of theo-science represents the integration of revelation, reason, and scientific observation in interpreting ayat kauniyah, particularly QS. Al-Anbiyā’ [21]:30. It also highlights the relevance of this integration in building an Islamic scientific paradigm grounded in the principles of tawhid and scientific rationality. This research adopts a qualitative method with a descriptive approach and is classified as library research. Data were collected through an in-depth review of primary and secondary sources, followed by content analysis and hermeneutic interpretation of verses and tafsir texts to explore the epistemological relationship between revelation and science. The findings indicate that Agus Purwanto interprets QS. Al-Anbiyā’ [21]:30 through an integrative approach that unites revelation, reason, and scientific observation. Rather than merely aligning the verse with modern scientific theories, he positions the Qur’an as the epistemological foundation of scientific knowledge. Through the theo-scientific paradigm, this study affirms that scientific inquiry into the universe is, in essence, an acknowledgment of God’s oneness and greatness.